Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1074/jbc.271.45.28112
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mutational Analysis of the Double-stranded RNA Binding Domains of Xenopus laevis RNA-binding Protein A

Abstract: Xenopus laevis RNA-binding protein A is a ubiquitously expressed, double-stranded RNA-binding protein that is associated with the majority of cellular RNAs, ribosomal RNAs, and hnRNAs. X. laevis RNA-binding protein A contains three copies of the double-stranded RNA-binding domain (dsRBD) in tandem arrangement. Two of them, xl1 and xl2, belong to the type A group of dsRBDs that show strong homologies to the entire length of a defined consensus sequence. The xl3 domain, in contrast, is a type B dsRBD which only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 28 publications
(70 reference statements)
6
96
0
Order By: Relevance
“…10 (lanes 12 and 13), Ubx Ib binds DNA with a single consensus binding site of 5Ј-TAATGG-3Ј (57) to generate a single shifted band. Under the same conditions, only a small degree of DIP1-c⅐DNA binding was observed, consistent with the general ability of dsRBDs to weakly interact with dsDNA (37,38,50). However, when DIP1-c and Ubx Ib are combined, a novel DNA complex is observed.…”
Section: Ubx Ib and Dip1-c Form A Ternary Complex On Ubxsupporting
confidence: 76%
See 2 more Smart Citations
“…10 (lanes 12 and 13), Ubx Ib binds DNA with a single consensus binding site of 5Ј-TAATGG-3Ј (57) to generate a single shifted band. Under the same conditions, only a small degree of DIP1-c⅐DNA binding was observed, consistent with the general ability of dsRBDs to weakly interact with dsDNA (37,38,50). However, when DIP1-c and Ubx Ib are combined, a novel DNA complex is observed.…”
Section: Ubx Ib and Dip1-c Form A Ternary Complex On Ubxsupporting
confidence: 76%
“…Importantly, two dsRBDs (residues 171-237 and 335-403) (50) were also identified in DIP1. dsRBDs are 65-68-amino acid motifs that are divided into two categories: type A domains, which are conserved throughout the motif in sequence and secondary structure of ␣-␤-␤-␤-␣ (where ␣ denotes ␣-helix and ␤ is ␤-sheet), and type B domains, which are only conserved in the C-terminal helix (37,50). Interestingly, the first dsRBD of DIP1 is a type A domain whereas the second dsRBD is a type B domain (data not shown) (24).…”
Section: Identification Of Functional Motifs Within the Dip1mentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is not unique to dADAR dsRBD1, as the stacking of positively charged residues equivalent to K110 and R114 (dADAR dsRBD1 residue numbering - Figure 3E) over conserved aromatic rings, namely Y78 for K110 and F92 for R114, allows these long side chains to adopt an elongated conformation ( Figure 6). It has been proposed earlier that these aromatic side chains would therefore be essential for proper orientation of the long positively charged residues within the KKxAK consensus motif at the N-terminal tip of helix α2 [32], and their importance for the dsRNA binding capacity of dsRBDs have been also demonstrated [30,33,56]. Surprisingly, the side chain of K111 also presents an elongated conformation in the free form which in this case cannot be explained by a stacking onto an aromatic residue.…”
Section: Modelling the Interaction Of Drosophila Adar Dsrbd1 With Rnamentioning
confidence: 87%
“…The NMR structure of the Staufen dsRBD has been solved (23), as has the crystal structure of the Xlrbpa dsRBD complexed with dsRNA (24). Saturation mutagenesis studies on the dsRBD of Xlrbpa demonstrated that the substitution of a conserved central Phe residue by Ala in both Staufen and Xlrbpa dsRBDs leads to abolition of RNA binding activity (23,25). Reference to the published structure of the dsRBD-RNA complex demonstrates that this residue is important in stabilizing a lysine side chain that makes important backbone contacts adjacent to the major groove (24).…”
mentioning
confidence: 99%